2007
DOI: 10.2165/00003495-200767100-00007
|View full text |Cite
|
Sign up to set email alerts
|

Medication Noncompliance and its Implications in Transplant Recipients

Abstract: The transplant patient's therapeutic regimen consists of a lifelong drug therapy, including immunosuppressive drugs, prophylactic antimicrobials and often medications for the treatment of hypertension, diabetes mellitus and other comorbid diseases. Regular clinic appointments are required to monitor for signs and symptoms of immunological injury, recurrent disease and adverse drug effects. Patients are instructed to avoid risk factors for cardiovascular disease and cancer (e.g. diet, exercise, sun protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 54 publications
1
90
1
7
Order By: Relevance
“…Simpler dosing regimens have been shown to facilitate better adherence behavior (1,2). Potential advantages of improved adherence and more consistent exposure with the extended release profile of tacrolimus QD (3)(4)(5)(6)(7) include a reduction in rejection and graft loss (8)(9)(10) on longer-term follow-up.…”
Section: Prograf (Astellas Pharma Europe Ltd Staines Uk; Hereafter mentioning
confidence: 99%
“…Simpler dosing regimens have been shown to facilitate better adherence behavior (1,2). Potential advantages of improved adherence and more consistent exposure with the extended release profile of tacrolimus QD (3)(4)(5)(6)(7) include a reduction in rejection and graft loss (8)(9)(10) on longer-term follow-up.…”
Section: Prograf (Astellas Pharma Europe Ltd Staines Uk; Hereafter mentioning
confidence: 99%
“…13 Simpler dosing regimens facilitate better adherence behavior, reducing graft rejection and loss on longer-term follow-up. 14,15 Previous studies in healthy volunteers showed that twice-daily and once-daily tacrolimus regimens that maintain equivalent total daily doses result in similar exposures to the drug. Furthermore, clinical trials in transplant recipients that substituted one formulation for the other but retained the same total daily dose demonstrated equivalent exposure and similar ratios of C min to AUC0-24 for twice-daily and once-daily tacrolimus.…”
Section: Figure 1 Liver Transplantation At Başkent Universitymentioning
confidence: 99%
“…It is estimated that non adherence to long-term medication is as high as 50% in developed countries and higher in developing countries (76). Risk factors for nonadherence include nonadherence behavior prior to transplantation, psychiatric illness, personality disorders, poor social support, substance abuse and other high-risk behavior, adolescence, high education level, time since transplantation, lack of adequate follow-up with transplant specialists, inadequate pretransplant education, multiple adverse effects from medications, complex medication regimens, expensive medications and poor access to healthcare (23,75,77).…”
Section: Adherencementioning
confidence: 99%